2010
DOI: 10.1111/j.1468-2494.2009.00533_5.x
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of 18‐MEA onto alkaline‐color‐treated weathered hair to form a persistent hydrophobicity

Abstract: incorporation into an o/w emulsion at 8% yielded increased viscosity and reduced emulsion droplet size as compared to the emollient ester CCT (capric/caprylic triglyceride) or a control formulation. Quantitative data indicate that application of the o/w emulsion formulation containing either HP or CCT significantly elevated skin moisture content and thus reduced transepidermal water loss (TEWL) by a maximal 33% against the control formulation within 3 h and maintained this up to 6 h. Visual observation of skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Our previous work found that the treatment with 18‐MEA combined with SPDA provided hydrophobicity to the damaged hair, and that this property was maintained even after shampooing 12. ToF‐SIMS analyses and dynamic contact angle measurements were performed for hair treated with two conditioner formulas, 18‐MEA/DAPS and 18‐MEA/SPDA, and the relationship between surface hydrophobicity and the adsorption state of 18‐MEA was examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work found that the treatment with 18‐MEA combined with SPDA provided hydrophobicity to the damaged hair, and that this property was maintained even after shampooing 12. ToF‐SIMS analyses and dynamic contact angle measurements were performed for hair treated with two conditioner formulas, 18‐MEA/DAPS and 18‐MEA/SPDA, and the relationship between surface hydrophobicity and the adsorption state of 18‐MEA was examined.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between the damage level of 18‐MEA and hair hydrophobicity was analyzed, and the influence of the 18‐MEA condition on hair hydrophobicity was examined. Furthermore, we developed a method for the regeneration of 18‐MEA on damaged hair surfaces and found that an 18‐MEA conditioner treatment combined with stearoxypropyldimethylamine (SPDA) effectively results in persistent hydrophobicity and low friction on damaged hair surfaces 12. ToF‐SIMS analyses were performed on conditioner‐treated hair, and the effect of the adsorption state on the surface hydrophobicity was examined.…”
Section: Introductionmentioning
confidence: 99%
“…Concretely, it is thought that there arise physical changes such as decreasing the tensile strength of hair fibers 14) and increasing the friction on hair surfaces 15) , and some c hemical changes such as decreasing 18-methyleicosanoic acid 16) which is a specific hair lipid, and increasing cysteic acid by the oxidative cleavage of the disulfide bond of cystine 12) .…”
Section: A Change Of the Electronic Density Caused By Bleach Relatinmentioning
confidence: 99%
“…The surface damage of hair leads to changes in the physical properties such as increase in hydrophilicity and friction, which decreases hair quality. In previous studies it was revealed that serious damage leading to cleavage of disulfide bonds in cystine and decreasing of the fatty acids occur on the hair surface as shown in Fig. .…”
Section: Introductionmentioning
confidence: 99%